2014
DOI: 10.5888/pcd11.130237
|View full text |Cite
|
Sign up to set email alerts
|

From Menu to Mouth: Opportunities for Sodium Reduction in Restaurants

Abstract: Restaurant foods can be a substantial source of sodium in the American diet. According to the Institute of Medicine, the significant contribution made by restaurants and food service menu items to Americans’ sodium intake warrants targeted attention. Public health practitioners are uniquely poised to support sodium-reduction efforts in restaurants and help drive demand for lower-sodium products through communication and collaboration with restaurant and food service professionals and through incentives for res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Restaurant foods can be an important source of sodium in the diet. Restaurant foods can contribute nearly to 25% of the sodium consumed [ 11 , 48 ]. A study proposed Strategies to Encourage Sodium Reduction in Restaurants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Restaurant foods can be an important source of sodium in the diet. Restaurant foods can contribute nearly to 25% of the sodium consumed [ 11 , 48 ]. A study proposed Strategies to Encourage Sodium Reduction in Restaurants.…”
Section: Discussionmentioning
confidence: 99%
“…The need for efforts to make restaurants to reduce consumer sodium exposure and to generate greater consumer awareness on how much sodium is in foods consumed away from home is noteworthy. However, there is a challenge for restaurant employees which is the lack of standardized recipes and the lack of employee knowledge about the importance of the SC on consumer health [ 11 , 29 ]. Recipe analysis and subsequent menu-labeling require cost and time, which can be a barrier to consumer information [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis showed that many large chain restaurants have not made meaningful progress to reduce the fat, saturated fat, added sugars and especially the sodium content of offerings to align with recommended targets for meals sold to children, adolescents and parents. Technical assistance is available to help restaurants meet these nutrient targets [ 130 ]. Some research suggests that consumers will accept restaurants making modest and gradual recipe changes to items over time to reduce total calorie, fat and sodium intake [ 131 ].…”
Section: Discussionmentioning
confidence: 99%